2014
DOI: 10.1177/1533317514536600
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Stimulation of Taichong (Liv3) and Hegu (LI4) Modulates the Default Mode Network Activity in Alzheimer’s Disease

Abstract: It was found that the acupuncture stimulation could modulate the DMN activity in AD. The current findings suggest that the acupuncture treatment on the relative earlier AD patients might have a better therapy effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 34 publications
1
52
0
1
Order By: Relevance
“…Studies have partially clarified the mechanisms by which acupuncture can prevent AD through anti-inflammatory (Ding et al, 2017), anti-oxidative (Sutalangka et al, 2013), and anti-apoptotic effects (Guo et al, 2015(Guo et al, , 2016. Moreover, acupuncture can modulate the functional activity and connectivity of specific cognition-related areas of the brain in AD patients (Wang et al, 2012Liang et al, 2014;Zheng et al, 2018). However, the effect of manual acupuncture (MA) on CBF in AD therapy and the specifics of its molecular mechanisms are still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have partially clarified the mechanisms by which acupuncture can prevent AD through anti-inflammatory (Ding et al, 2017), anti-oxidative (Sutalangka et al, 2013), and anti-apoptotic effects (Guo et al, 2015(Guo et al, , 2016. Moreover, acupuncture can modulate the functional activity and connectivity of specific cognition-related areas of the brain in AD patients (Wang et al, 2012Liang et al, 2014;Zheng et al, 2018). However, the effect of manual acupuncture (MA) on CBF in AD therapy and the specifics of its molecular mechanisms are still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis not only supports the high safety of the technique but also indicates that acupuncture is more effective than drugs at improving AD patients' ability to carry out their daily lives and may even enhance the effects of drug treatments [ 2 ]. fMRI studies have shown that acupuncture can enhance hippocampal connectivity [ 3 ], modulate default mode network activity [ 4 ], and activate certain cognitive-related regions in AD patients [ 5 ]. The positive effect of acupuncture on blood perfusion and glycol metabolism in certain brain areas in a rat model of AD has also been certified by PET studies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The psychological assessment on the participants was performed in 4 studies [21, 31, 46, 92, 93]. The self-rating depression scale (SDS) and the self-rating anxiety scale (SAS) were used in 2 studies [31, 46].…”
Section: Resultsmentioning
confidence: 99%
“…38 studies [11, 13, 15, 21, 31, 36, 42, 43, 46, 54, 57, 64, 65, 68, 73, 76, 78, 81, 87, 93, 100, 102, 104, 106, 110121, 123, 128, 133, 135, 141, 148, 151, 153, 156, 158, 165, 174] excluded the participants with head trauma, and some studies [24, 46, 54, 73, 100, 121, 122] excluded the participants suffering from pain (including headache and dysmenorrhea).…”
Section: Resultsmentioning
confidence: 99%